2003
DOI: 10.1021/la0259297
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Surface Analysis of Plasma-Deposited Tetraglyme for Reduction of Protein Adsorption and Monocyte Adhesion

Abstract: Adsorbed proteins on implanted biomedical devices mediate platelet and leukocyte adhesion. Radio frequency plasma deposited tetraglyme (CH3O(CH2CH2O)4CH3), which forms a PEO-like coating, has been shown to resist protein adsorption and monocyte adhesion in vitro. By using different plasma deposition powers (5-80 W), we produced a series of plasma-deposited tetraglyme surfaces that varied in surface chemistry as measured by electron spectroscopy for chemical analysis (ESCA) and time-of-flight secondary ion mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
155
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(164 citation statements)
references
References 31 publications
8
155
1
Order By: Relevance
“…From the literature, we can estimate that this level of nitrogen on the surface corresponds to <10 ng/cm 2 of protein. 47 These values are commensurate to results from a number of previous studies using ppTTg coatings 44,47,49 and match with the ELISA results discussed previously. Together this data suggest that coatings are able to retain significant functionality on PDMS even after extended periods of dry shelf storage.…”
Section: Functionality Of Ppttg Coatingssupporting
confidence: 83%
See 2 more Smart Citations
“…From the literature, we can estimate that this level of nitrogen on the surface corresponds to <10 ng/cm 2 of protein. 47 These values are commensurate to results from a number of previous studies using ppTTg coatings 44,47,49 and match with the ELISA results discussed previously. Together this data suggest that coatings are able to retain significant functionality on PDMS even after extended periods of dry shelf storage.…”
Section: Functionality Of Ppttg Coatingssupporting
confidence: 83%
“…This similarity between the precursor and deposited film composition is particularly important for the ethylene oxide-based protein resistant films used here, as the non-fouling properties have been directly linked to the ether carbon content of the film. Shen et al 47,49 and Johnston et al 58 have shown that the higher the content of ether carbon, the more functional the coatings become, and the less protein they adsorb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This adsorption layer can lead to complications such as leukocyte adhesion or blood coagulation, which may impair the function of the device and limit its therapeutic effects [157]. Its noteworthy that as little as 10 ng/cm 2 of fibronectin can induce substantial platelet adhesion [158]. Polymer brush type, density and length are variables that can be manipulated to produce a stable, low fouling surface.…”
Section: Low Fouling Brushes For Controlling Materials Interactionsmentioning
confidence: 99%
“…To date, most studies of plasma-modified biomaterials make use of a large-volume plasma reactors to modify the surface of a small disk or film substrate. [3][4][5][6] However, such reactors are not very practical for surface modification of small diameter tubing 1 and many small-scale biomedical devices. 9 This is because the plasma tends to quench itself near the ends of the tubing, 7,8 when placed in a large-volume reactor, and thus only small portions near the ends of the tube are treated.…”
Section: Introductionmentioning
confidence: 99%